Body Fat Percentage Prediction Model of Female Republic of Indonesia Defense University Cadet - Dwi Monik Purnamasari; Rachma Hidana; Yolanda Safitri; Elies Fitriani; Handrian Rahman Purawijaya; Grace Joselini Corlesa; Alfa Januar Krista; Ahmad Syafiq (Journal of Healthcare and Biomedical Science, 2024)
The incidence of obesity among female adolescents and adults continues to rise in Indonesia, posing significant health risks, such as cardiovascular diseases. Female cadets at the Republic of Indonesia Defense University (RIDU) are reserve members in national defense, and their performance is correlated with their nutritional status; therefore, their nutritional status should be closely monitored. Anthropometric examination is a method for nutritional assessment that incorporates body fat percentage (BFP) as part of body composition analysis. Predictive models for BFP can help identify obesity rates within a population. In Indonesia, no research has focused on BFP prediction models specifically for female RIDU cadets. This study aimed to develop a model to estimate BFP in this group. Conducted in August 2021, the research employed a quantitative cross-sectional approach involving 108 female students aged 18 to 20 from RIDU who met the inclusion and exclusion criteria. The study analyzed the relationship between BFP (measured by bioelectrical impedance analysis, or BIA) and independent variables such as age, body mass index (BMI), and waist circumference (WC). Pearson correlation tests and multivariate linear regression were used to create the prediction model. Findings showed an average BFP of 28.303% ± 6.37%. BMI had the strongest correlation with BFP (r = 0.722). The resulting predictive model is BFP = -94.055 + 39.064*WC + 1.073*age + 1.420*BMI, with an adjusted R square value of 0.535, indicating the model’s explanatory power. This study showed the first to predict BFP in female RIDU cadets. Age, BMI, and WC were predictors of BFP among female RIDU cadets.